Radiopoetik des sozialistischen Realismus: Sowjetische Autor_innen zwischen individuellem und kollektivem Sprechen - Monteiro, Oxana (transcript, 2018)
The Soviet radio and the development of socialist realism – Oxana Monteiro analyzes new forms of literary narrative as a result of radio phonics.